Achieving the Millennium Development Goals - McGillivray, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
This book provides analytical insights into if and how the targets adopted by the international community are likely to be achieved. A key feature of the analysis is the recognition that most of the MDG targets are endogenously related. These inter-dependencies are crucial not only in analysing the MDGs but also devising strategies.
Keywords: Development economics; International economics; Development Economics; International Economics